(untitled) (Heritage, 2020)
Various linguistic means characterize women’s language and they were presented to the public in the 70-ies. The first systematic and critical approach to linguistic features of women’s language were presented in a pioneering study by Robin Lakoff in 1975. Ever since, it has been considered as a beginning of a new interdisciplinary field of “gender studies”. Nowadays, women’s language presents an important issue of sociolinguistic studies of language and gender. This paper analyses the means for expressing modality in women’s language found in literary discourse. The corpora are comprised of seven novels about Harry Potter in English and Serbian alike. According to some theoreticians of language and gender, frequent use of epistemic modality presents a significant trait of women’s linguistic pattern (Coates, 1996, 2003; Мills, 1995; Livia, 2003). If we assume that attitudes and ideologies could be expressed by linguistic features such as modality, this paper aims to compare the modal forms and their meaning in English and Serbian by using contrastive linguistic analysis, determine the differences in linguistic patterns between the two and attempt to explain possible ideological implications from the CDA perspective.